Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1088/0953-8984/28/7/075402
|View full text |Cite
|
Sign up to set email alerts
|

A-thermal elastic behavior of silicate glasses

Abstract: Depending on the composition of silicate glasses, their elastic moduli can increase or decrease as function of the temperature. Studying the Brillouin frequency shift of these glasses versus temperature allows the a-thermal composition corresponding to an intermediate glass to be determined. In an intermediate glass, the elastic moduli are independent of the temperature over a large temperature range. For sodium alumino-silicate glasses, the a-thermal composition is close to the albite glass (NaAlSi3O8). The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…). Such glasses with nearly temperature‐independent elastic moduli are called intermediate glasses, which have attracted much attention in recent literature with a potential to develop athermal Brillouin fibers for sensor applications …”
Section: Discussionmentioning
confidence: 99%
“…). Such glasses with nearly temperature‐independent elastic moduli are called intermediate glasses, which have attracted much attention in recent literature with a potential to develop athermal Brillouin fibers for sensor applications …”
Section: Discussionmentioning
confidence: 99%
“…Brillouin longitudinal frequency shift of albite glass, a glass derived from the naturally occurring sodium feldspar, was found to remain constant with temperature . Although albite is an extensively studied glass in the geology community, all of its elastic constants at high temperature have not been reported to our best knowledge . By using in situ high‐temperature Brillouin light scattering (BLS) technique in this study, we found that all of the elastic moduli of albite glass remain constant up to its glass transition temperature ( T g ) and above.…”
Section: Introductionmentioning
confidence: 69%
“…Mechanically modified silica glass by a systematic pressure quenching was found to exhibit intermediate behavior without chemical modification . Brillouin longitudinal frequency shift of albite glass, a glass derived from the naturally occurring sodium feldspar, was found to remain constant with temperature . Although albite is an extensively studied glass in the geology community, all of its elastic constants at high temperature have not been reported to our best knowledge .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…In between, intermediate glass with temperature or pressure independent elastic moduli can be obtained. [6][7][8][9] In this study, by either pressurequenching, helium-stuffing, or alkali-modifying silica glass, we can change its elastic response to pressure systematically, i.e., to have a negative, zero, and positive slope. Then, by scrutinizing the structural differences among these three types of glasses in molecular dynamics (MD) simulations, we uncovered the structural origin of the elastic anomaly in silica glass, which can be attributed to localized structural transitions, analogous to those that occur in its crystalline counterparts.…”
Section: Introductionmentioning
confidence: 99%